What de teacher say? Talk as a mode of inquiry in curriculum enactment in a technical-vocational classroom - Harry, Sharmila Nisha; Smith, Tricia Lorraine (School of Education, UWI, St. Augustine, 2013)
This article examines the modes of triadic dialogue that emerged between a technical-vocational teacher and a group of 14 fifth form students at a senior comprehensive school in Trinidad. It also explores the teacher's perspectives of the factors that influenced his talk during the practical sessions. Data collection techniques involved the use of classroom observations, as well as semi-structured follow-up interviews. Data analysis included discourse and conversation analysis, as well as the coding of data into themes and categories. The findings reveal that whole-class discussions dominated the hands-on practical sessions. In addition, greater monologic applications of the Initiation-Response-Evaluation (IRE) mode of triadic dialogue took precedence over Initiation-Response-Feedback/Follow-up (IRF) dialogic discourse. However, there was only one instance where dialogic engagement emerged from the IRF mode. Furthermore, the findings revealed that the lack of resources, time constraints, poor physical conditions, ineffective teacher training and professional development, lack of teacher knowledge and skills, and the examination structure were the factors that influenced the teacher's classroom talk
Keywords: Technical and vocational education and training; Secondary school students; Vocational education teachers; Classroom communication; Senior comprehensive schools; Language usage; Discourse analysis; Trinidad and Tobago